Guidelines on deep vein thrombosis of the Brazilian Society of Angiology and Vascular Surgery - Sobreira, Marcone Lima [UNESP]; Marques, Marcos Áreas; Paschoa, Adilson Ferraz; Ribeiro, Alcides José Araújo; Casella, Ivan Benaduce; Burihan, Marcelo Calil; Matielo, Marcelo Fernando; Soares, Rafael de Athayde; de Araujo, Walter Junior Boin; Joviliano, Edwaldo Edner; de Oliveira, Julio Cesar Peclat (FapUNIFESP (SciELO), 2024)
Deep vein thrombosis is one of the main causes of inpatient and outpatient morbidity, both in medical and surgical patients, significantly impacting mortality statistics and requiring prompt diagnosis so that treatment can be initiated immediately. This document was prepared and reviewed by 11 specialists certified by the Brazilian Society of Angiology and Vascular Surgery, who searched the main databases for the best evidence on the diagnostic (physical examination, imaging) and therapeutic approaches (heparin, coumarins, direct oral anticoagulants, fibrinolytics) to the disease.
Diretrizes sobre trombose venosa profunda da Sociedade Brasileira de Angiologia e Cirurgia Vascular
Keywords: anticoagulants; deep vein thrombosis; duplex Doppler ultrasonography; fibrinolysis; vena cava filters; venous thromboembolism